2022
DOI: 10.1002/14651858.cd006404.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Pyronaridine-artesunate for treating uncomplicated Plasmodium falciparum malaria

Abstract: Background The World Health Organization (WHO) recommends artemisinin‐based combination therapies (ACTs) to treat uncomplicated Plasmodium falciparum malaria. Concerns about artemisinin resistance have led to global initiatives to develop new partner drugs to protect artemisinin derivatives in ACT. Pyronaridine‐artesunate is a novel ACT. Objectives To evaluate the efficacy of pyronaridine‐artesunate compared to alternative ACTs for treating pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…10,11,37 In a meta-analysis of eight randomized clinical trials, ALT elevations greater than five times the ULN occurred in 1.1% (41/3785) of patients with uncomplicated malaria, with one reported case in which raised ALT occurred with raised bilirubin. 24 However, to our knowledge, no study reported severe drug-induced liver injury in patients with malaria with PYR-AS. 24 Examination of the hypertransaminasemia cases by two independent liver safety experts concluded that there was no clear difference between the observed increases in ALT/AST in this study versus previous reports with PYR-AS in healthy White patients or patients with malaria.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…10,11,37 In a meta-analysis of eight randomized clinical trials, ALT elevations greater than five times the ULN occurred in 1.1% (41/3785) of patients with uncomplicated malaria, with one reported case in which raised ALT occurred with raised bilirubin. 24 However, to our knowledge, no study reported severe drug-induced liver injury in patients with malaria with PYR-AS. 24 Examination of the hypertransaminasemia cases by two independent liver safety experts concluded that there was no clear difference between the observed increases in ALT/AST in this study versus previous reports with PYR-AS in healthy White patients or patients with malaria.…”
Section: Discussionmentioning
confidence: 89%
“…24 However, to our knowledge, no study reported severe drug-induced liver injury in patients with malaria with PYR-AS. 24 Examination of the hypertransaminasemia cases by two independent liver safety experts concluded that there was no clear difference between the observed increases in ALT/AST in this study versus previous reports with PYR-AS in healthy White patients or patients with malaria. 10,11,20,[24][25][26][37][38][39][40][41] For this limited number of cases, there was no evidence that PQP co-administration increased the incidence or severity of PYR-induced ALT/ AST elevations or that sub-Saharan Africans were more at risk compared with previous reports of PYR-induced ALT/AST elevations in healthy White subjects.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations